Educational Centres of the Ukrainian National Minority in the Warmian-Masurian Province as Subjects of the Formation of Personal Security and Identity - Astramowicz-Leyk, Teresa; Turchyn, Yaryna; Ivasechko, Olha (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2024)
The article analyses the peculiarities of the functioning of educational centres of the Ukrain ian national minority in the Warmian-Masurian Province – the complex of schools in Gorowo Ilawieckie and the school named after Lesya Ukrainka in Bartoszyce. The historical aspects of the establishment and development of such schools, their problems and perspectives of functioning have been considered. The purpose of the article is to study the peculiarities of the functioning of educational centres of the Ukrainian national minority in Gorowo Ilawieckie and Bartoszyce, the legal basis, possibilities and prospects of their activity. The thesis that the new educational initiatives introduced in the legislative acts of Poland and the activation of migration have an impact on the functioning of educational centres for studying in the language of national minorities and learning the language of national minorities is the research hypothesis of the article. The research problem includes the following questions: 1. What changes in the educational processes of studying in the native language and learning the native language have new legislative initiatives in Poland led to?; 2. Are these centres able to face the new challenges associated with the migration of Ukrainians? The methodological basis of the research is the institutional and legal method, the method of focused interviewing, the method of specific situations, the systemic and historical method. W artykule przeanalizowano specyfikę funkcjonowania placówek oświatowych ukraińskiej mniejszości narodowej w województwie warmińsko-mazurskim – Zespole Szkół w Górowie Iławeckim oraz Szkole im. Łesi Ukrainki w Bartoszycach. Rozważono historyczne aspekty powstania i rozwoju takich szkół, ich problemy i perspektywy funkcjonowania. Celem artykułu jest zbadanie specyfiki funkcjonowania ośrodków edukacyjnych ukraińskiej mniejszości narodowej w Górowie Iławeckim i Bartoszycach, ram prawnych, możliwości i perspektyw ich działalności. Hipotezą badawczą artykułu jest twierdzenie, że nowe inicjatywy edukacyjne wprowadzone do polskiego ustawodawstwa oraz nasilenie migracji mają wpływ na funkcjonowanie ośrodków edukacyjnych nauczania w językach mniejszości narodowych i nauki języków mniejszości narodowych. Problem badawczy obejmuje następujące pytania: 1) Jakie zmiany w procesach edukacyjno-wychowawczych nauczania języka ojczystego i uczenia się języka ojczystego spowodowały nowe inicjatywy legislacyjne w Polsce?; 2) Czy ośrodki te są w stanie wytrzymać nowe wyzwania związane z migracją Ukraińców? Podstawą metodologiczną badania jest metoda instytucjonalno-prawna, metoda wywiadów zogniskowanych, metoda konkretnych sytuacji, metoda systemowa i historyczna.
Ośrodki edukacyjne ukraińskiej mniejszości narodowej w województwie warmińsko-mazurskim jako podmioty kształtowania bezpieczeństwa i tożsamości osobistej
Keywords: Ukrainian national minority; educational centres; Ukrainian schools; native language; Warmian-Masurian Province; ukraińska mniejszość narodowa; ośrodki edukacyjne; szkoły ukraińskie; język ojczysty; województwo warmińsko-mazurskie